The Effect of The Archival System on The Effectiveness of Employee Work at The Cirebon Regency Industry and Trade Office - Merlinda Intan Fauziah; Gita Prabawati Azzahra (PT. Publikasiku Academic Solution, 2025)
A good filing system is an important factor in supporting the smooth running of work and improving the efficiency of employees in government agencies. At the Cirebon Regency Industry and Trade Office, an optimal filing system is still a challenge. This study aims to analyze the effect of the filing system on employee work effectiveness. This study uses a quantitative method with a survey approach. Data was collected through questionnaires distributed to 89 employees from various educational strata at the Industry and Trade Office. The results showed that a good filing system, including efficient storage, management, and retrieval of files, has a positive and significant effect on employee work effectiveness. The filing system score was 3545, which indicates a fairly good category, but not yet optimal. Although the filing system at the Cirebon Regency Industry and Trade Office is quite good, there are still aspects that need improvement, especially in the maintenance and depreciation of archives. This study suggests that further analysis be conducted on other factors that affect work effectiveness and solutions to improve filing facilities.